Keterkaitan antara Miskonsepsi dan Kemampuan Literasi Sains Peserta Didik pada Materi Pemanasan Global - Eva Aini; Evendi Evendi; A. Halim; M. Syukri; Yusrizal Yusrizal (Postgraduate, University of Mataram, 2023)
This study aims to identify misconceptions experienced by students, the level of scientific literacy skills and the relationship between misconceptions and scientific literacy skills on global warming. The research method used is correlational research with a quantitative approach. The sample selected was 80 students using purposive sampling technique. The instrument used was 10 items to measure misconceptions with a four-tier multiple choice diagnostic test and 10 test items to measure scientific literacy skills. The results of the analysis of misconceptions with CRI showed that the category of misconceptions was 44% with moderate criteria, students who understood the concept were 32% and did not understand the concept by 32%. The results of the analysis of scientific literacy skills obtained an average value of 40.65, a percentage of 40.7% and is in the low category after interpretation. The aspect of scientific literacy that is measured in the highest percentage is the context aspect with an average percentage of 48.1%, the knowledge aspect is 40.4% and the competence aspect is 34.1%. The results of the analysis of the relationship between misconceptions and scientific literacy skills were carried out using the Pearson product moment correlation test which showed a positive and significant relationship with a significant value of 0.008 < 0.05 and a large correlation value of 0.270 with a low category. Based on the hypothesis test, the results show that there is a positive relationship between misconceptions and scientific literacy skills with tcount 2.476 > ttable 1.990.